Analisis Kepentingan Tiongkok melalui Proyek East Coast Rail Link di Malaysia dalam Tinjauan Konektivitas Geopolitik - prasodjo, haryo (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2023)
The East Coast Rail Link (ECRL) is a strategic project between China and Malaysia. Become an alternative rail network project, after the completion of the Malaysia-Singapore fast train project. The ECRL project connects the East and West sides of Malaysia, encompassing several economic zones. In contrast to the Malaysian high-speed rail project, even though the ECRL has faced a lot of opposition, and several times the negotiation process, the ECRL project continues. Using a connectivity geopolitical approach, and qualitative analysis, this study aims to analyze China's interest in the ECRL project. The time limit is from 2016 to 2022, with data collection techniques through literature studies. The findings of this study are that there is interest in geopolitics and geoeconomics, especially in building alternative routes to reduce China's dependence on the Malacca Strait.